Prediction Studies of River Water Quality Based on Moving Average Weighted Markov Model – A Case Study of Shiwei Port, Jingjiang City. Issue 1 (January 2021) - Jiao, Kuo; Cheng, Liang; Tao, Ya; Chen, Peng; Chen, Wei
Abstract: It is of great significance to predict the change trend of river water quality and comprehensively prevent and control river pollution for the protection of water quality of the Yangtze River and the implementation of "to step up conservation of the Yangtze River and stop its over development". Shiwei Port of Jingjiang City is located in the middle of Jingjiang City. It runs from north to south, connects the Jingtai Boundary River in the north, and enters the Yangtze River in the south. It is a first-class tributary of the Yangtze River. Based on the Moving Average Weighted Markov Model, this paper conducts an applied research on the water quality of Shiwei Port flowing into the Yangtze River. It is found that with the increase of the moving step, the accuracy of the moving prediction increases gradually, and the highest accuracy of the moving prediction is 24.9% compared with the original data, which shows that the moving average is necessary for the weighted Markov water quality prediction. Finally, the problems of the prediction model are analyzed and discussed, and the corresponding suggestions for the water quality and environmental management of Jingjiang City where Shiwei port is located are put forward, which can provide reference for the water quality management of other cities on both sides of the Yangtze River.